International Monetary Fund Annual Report 1965. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1965)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1965. The report highlights that in many respects, the year 1964 was a highly satisfactory one for the world economy. World industrial production and, in particular, international trade-including the exports of the primary producing countries-were substantially higher than in the preceding year. However, within 1964, there was a slowing down of economic activity in several major countries, and the rate of increase in world trade was somewhat lower than during the preceding year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet